High Resolution Intravital Imaging of the Renal Immune Response to Injury and Infection in Mice - Sedin, John; Giraud, Antoine; Steiner, Svava E.; Ahl, David; Persson, A. Erik G.; Melican, Keira; Richter-Dahlfors, Agneta; Phillipson, Mia (Frontiers in Immunology, 2019)
We developed an experimental set up that enables longitudinal studies of immune cell behavior in situ in the challenged as well as unchallenged kidney of anesthetized mice over several hours. Using highly controlled vacuum to stabilize the kidney, the superficial renal cortex could continuously be visualized with minimal disruption of the local microenvironment. No visible changes in blood flow or neutrophils and macrophages numbers were observed after several hours of visualizing the unchallenged kidney, indicating a stable tissue preparation without apparent tissue damage. Applying this set up to monocyte/macrophage (CX3CR1GFP/+) reporter mice, we observed the extensive network of stellate-shaped CX3CR1 positive cells (previously identified as renal mononuclear phagocytes). The extended dendrites of the CX3CR1 positive cells were found to bridge multiple capillaries and tubules and were constantly moving. Light induced sterile tissue injury resulted in rapid neutrophil accumulation to the site of injury. Similarly, microinfusion of uropathogenic Escherichia coli into a single nephron induced a rapid and massive recruitment of neutrophils to the site of infection, in addition to active bacterial clearance by neutrophils. In contrast, the kidney resident mononuclear phagocytes were observed to not increase in numbers or migrate toward the site of injury or infection. In conclusion, this model allows for longitudinal imaging of responses to localized kidney challenges in the mouse.